Chinese herbal medicines for treating ulcerative colitis via regulating gut microbiota-intestinal immunity axis - Yifei Yang; Yi Wang; Long Zhao; Fang Wang; Mingxing Li; Qin Wang; Haoming Luo; Qianyun Zhao; Jiuping Zeng; Yueshui Zhao; Fukuan Du; Yu Chen; et al. (2023)
Ulcerative colitis (UC) is one of types of inflammatory bowel disease with high recurrence. Recent studies have highlighted that microbial dysbiosis as well as abnormal gut immunity are crucial factors that initiate a series of inflammatory responses in the UC. Modulating the gut microbiota-intestinal immunity loop has been suggested as one of key strategies for relieving UC. Many Chinese herbal medicines including some of single herb, herbal formulas and the derived constituents have been reported with protective effect against UC through modulating gut microbiome and intestinal immunity. Some clinical trials have shown promising results. This review thus focused on the current knowledge on using Chinese herbal medicines for treating UC from the mechanism aspects of regulating intestinal homeostasis involving microbiota and gut immunity. The existing clinical trials are also summarized.